Biodegradation of insecticides: oligonucleotide insecticides and double-stranded RNA biocontrols paving the way for eco-innovation - Oberemok, Vol V.; Laikova, Kateryna V.; Andreeva, Oksana A.; Gal’chinsky, Nikit V. (Frontiers in Environmental Science, 2024)
Each new class of insecticides that emerged during the development of plant protection gradually found the most suitable group of insect pests for application. At the same time, for each individual insecticide, a balance was sought between its effectiveness, on the one hand, and its safety for nontarget organisms and the ecosystem as a whole, on the other hand. Neonicotinoids, diamides and pyrethroids, as effective control agents, dominate the insecticide market, but do not have outstanding performance in selectivity and biodegradation. The biodegradation of insecticides is one of the most important indicators, representing what will be said about the hidden costs for the resulting harvest paid by the environment and human health. Oligonucleotide insecticides (contact unmodified antisense DNA (CUAD) biotechnology, or 'genetic zipper' method) and RNA biocontrols (doublestranded RNA technology) as natural polymers and the next-generation classes of insecticides possess unique characteristics in fast biodegradation and high selectivity in action. While current chemical insecticides require days, months and even years for biodegradation by bacteria and fungi, oligonucleotide insecticides and RNA biocontrols are substantially biodegraded within hours in the presence of nucleases. Nucleic acid-based insecticides have the potential to complement the existing insecticide market and set an eco-precedent for crop protection products where the effectiveness of the insecticide will be determined by its safety for non-target organisms, and other factors being equal, the choice of a particular control agent will be determined by its biodegradability. It should be noted that not a single class of insecticides that once appeared has completely disappeared; rather, it has occupied its niche, gradually declining under the pressure of new classes of insecticides. At the same time, the common trend in plant protection is towards use of insecticides with higher biodegradability, which gives hope for a safer future of the planet.